2015
DOI: 10.7287/peerj.preprints.1443
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Homeotic transformations and number changes in the vertebral column of Triturus newts

Abstract: We explored intraspecific variation in vertebral formulae, more specifically the variation in the number of thoracic vertebrae and frequencies of transitional sacral vertebrae in Triturus newts (Caudata: Salamandridae). Within salamandrid salamanders this monophyletic group shows the highest disparity in the number of thoracic vertebrae and considerable intraspecific variation in the number of thoracic vertebrae. Triturus species also differ in their ecological preferences, from predominantly terrestrial to la… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…9-7 Ma) (Ivanović and Arntzen 2014;Wielstra et al 2019). The two species differ in adult morphology (e.g., body shape and coloration (Arntzen 2003;Vukov et al 2011) and the modal number of trunk vertebrae (Arntzen 2003;Slijepčević et al 2015)); some differences in larval tail morphology were also recorded (Vučić et al 2018). Triturus ivanbureschi and T. macedonicus reproduce in similar aquatic habitats (Džukić et al 2016).…”
Section: Model System and Experimental Settingsmentioning
confidence: 99%
See 3 more Smart Citations
“…9-7 Ma) (Ivanović and Arntzen 2014;Wielstra et al 2019). The two species differ in adult morphology (e.g., body shape and coloration (Arntzen 2003;Vukov et al 2011) and the modal number of trunk vertebrae (Arntzen 2003;Slijepčević et al 2015)); some differences in larval tail morphology were also recorded (Vučić et al 2018). Triturus ivanbureschi and T. macedonicus reproduce in similar aquatic habitats (Džukić et al 2016).…”
Section: Model System and Experimental Settingsmentioning
confidence: 99%
“…In eastern Serbia, a confirmed unimodal natural hybrid population is found, with Fn individuals that derived from multiple mutual crossings and backcrosses with parental species (Wielstra and Arntzen 2014;Wielstra et al 2014a;Arntzen et al 2018). Studies of Triturus newt hybrids showed that they have intermediate morphological traits relative to their parental species (e.g., Francillon-Vieillot et al 1990;Brede et al 2000;Vinšálková and Gvoždík 2007;Litvinchuk and Borkin 2009;Slijepčević et al 2015), including T. macedonicus × T. ivanbureschi hybrids (Vučić et al 2018;Arntzen et al 2018).…”
Section: Model System and Experimental Settingsmentioning
confidence: 99%
See 2 more Smart Citations
“…vertebrae with morphological characteristics of two adjacent regions (for example trunk and sacrum) are statistically underrepresented in these species. This suggests a developmental mechanism favouring complete numbers of trunk vertebrae, rather than transitional vertebrae that might hamper mechanical function (46,47). If additional trunk somites would form bilaterally via daughter somite formation, both newly created somites might have the same axial identity as their mother somite, given that the Hox identity is determined mainly before the somite is formed, during the earliest stages of somite formation (48)(49)(50).…”
Section: The Implications Of Somite Plasticity and Self-organization mentioning
confidence: 99%